Rotational properties of near-earth objects obtained by the IMPACTON project. (1st December 2018) - Monteiro, F.; Silva, J.S.; Lazzaro, D.; Arcoverde, P.; Medeiros, H.; Rodrigues, T.; Souza, R.
Abstract: To achieve a better understanding of the formation and evolution of the near-Earth objects (NEO) population, it is important to know the physical properties for a large sample of its members. Moreover, these properties are of upmost relevance in the case of objects that have a chance of hitting Earth. Photometric data for 60 NEO were obtained between 2012 and 2016 with the 1-m telescope of Observatório Astronômico do Sertão de Itaparica (OASI). The data were used to derive the rotational period, the spin direction, and an estimate of the shape of the observed asteroids. The rotational period was determined using a Fourier series analysis while the spin direction and the shape model were derived from a lightcurve inversion method. A reliable rotational period was derived for 42 NEOs, with values varying from 6 min up to 17 h and with lightcurve amplitudes between 0.1 and 1.85 mag. An indication for the period was obtained for other 16 objects while for 9 objects we derived the spin direction and the shape model. Our results are compared with those from the literature and show that some objects rotate quite fast for their size and that there is a tendency for retrograde rotation among the NEOs population. Highlights: For a sample of 42 NEOs was derived the rotational period with good reliability. The spin direction and a shape model were derived for 9 NEOs. Our data confirms a lack of spin axes in the direction of the ecliptic plane. We confirm the preference for retrograde rotation among the NEO population. In our sample, we found 9 objects that can be binary.